(untitled) (Dentika: Dental Journal, 2015)
Filling techniques influence in reducing polymerization shrinkage which cause microleakage. Besides, the use of matrices also contributes to achieve good marginal ridge. This study was aimed to examine the effect of filling techniques and the use of matrices on microleakage of saucer-shaped Class II restorations. Mandibular premolar specimens were prepared in saucer-shaped cavity design, then they were divided into eight groups according to filling techniques (bulk or incremental), the use of matrices (circumferential or sectional), and whether load was provided or not. Specimens were immersed in saline for 24 hours, then thermocycled, later immersed in 2% methylene blue for 24 hours. Micro gap was measured by scoring dye penetration in specimens that were sectioned mesio-distally under a stereomicroscope with 20x magnification. Furthermore, visual analysis was performed under Scanning Electron Microscope to examine the microleakage in details. Statistical analysis with Kruskal-Wallis test and Mann-Whitney test demonstrated that bulk and incremental filling techniques were not significantly different in microleakage (p> 0.05). This study also demonstrated that the use of matrices was significantly different in microleakage in different filling techniques (p< 0.05), whether load was provided or not. This study showed that the use of matrices was important in reducing the microleakage in saucershaped Class II restorations.